Arsenate decreases production of methylmercury across increasing sulfate concentration amendments in freshwater lake sediments. Issue 9 (7th June 2022) - Mija, Aždajić; Jules M, Blais; Alexandre J, Poulain
Abstract : Methylmercury production rates in freshwater sediments significantly decreased with increasing arsenate concentrations, regardless of sulfate concentrations amended to the sediments. Abstract : Arsenic (As) and sulfate pollution are often found co-occurring as a result of smelting metal ores. Previous studies showed that sulfate reducing microbes (SRMs) can use As(v ) as a terminal electron acceptor, while others reported that SRMs are the main mercury (Hg) methylators in freshwater systems. However, we have yet to fully explore how As(v ) can affect methylmercury (MeHg) production. In this study, we examined whether additions of As(v ) and sulfate in freshwater sediments collected near a major gold mine with a history of S and As emissions affect Hg methylation. First, we show that Hg methylation in lake sediments was primarily limited by carbon substrate availability rather than by that of sulfate as terminal electron acceptors. Then, under conditions where carbon is not limiting, sulfate addition to the system significantly increased Hg methylation rate constants. Finally, we show that MeHg production rates in sediments significantly decreased with increasing As(v ) concentrations, regardless of the sulfate concentration amended to sediments. This work underscores the apparent antagonistic effects of As(v ) on the one hand, and carbon and sulfate on the other hand on the kinetics of Hg methylation. Arsenic controls on Hg methylation are complex and a combination of direct impact on the methylators' fitness, the formation of As-bearing mineral phases affecting Hg bioavailability, or changes in the microbial community structures over increasing As concentrations should be the focus of additional investigations.